KONTRIBUSI KAPASITAS VITAL PARU TERHADAP DAYA TAHAN KARDIORESPIRATORI - Armen, Meiriani (Jurnal Endurance, 2017)
Development of science and technology of sports can be done by conducting research, transfer of technology, socialization, scientific meeting and cooperation among research institute having specialization of science and technology of sport. This study aims to see concretely the contribution of vital capacity of the lung to cardiorespiratory endurance. The population of this study is non-regular students of FIK UNPs education department who took athletic courses totaling 159 people. The sampling technique was done by proportional random sampling and got 32 samples. Data was collected at sport medicine laboratory and FIK UNP track, vital pulmonary capacity was measured by spirometer, cardiorespiratory assay test was measured by VO2 Max test of Balke method, calculated running distance for 15 minutes. Analysis of research data with product moment correlation technique with significant level Î± 0.05. The data were analyzed by excel and SPSS version 12. From the data analysis, it was found that there was "no significant relationship" between vital lung capacity and cardiorespiratory resistance, and the contribution was only 0.08%. So it can be concluded that the endurance ability kardiorespiratori not much determined by the vital capacity of the lung.